Application of some nonclassical methods for p-defocusing complex Klein-Gordon equation - Yokus, Asif; Iskenderoglu, Gulistan; Kaya, Dogan (Springer, 2023)
This research studies the high-energy Klein-Gordon equation, related to the relativistic Schrodinger wave equation. Solutions are produced using the Kudryashov transform and conventional wave transform. The study's most significant finding is the examination of the physical and mathematical differences in the traveling wave solutions, derived using two alternative transformations. The graphs of the intensity of the wave function and the conclusions at various velocity levels are also examined. The stability analysis of the moving waves, which coincides with Graham's diffusion law, of the relationship between wave velocity and density is examined and its relationship with the propagation equation is investigated.
Keywords: Partial differential equation; 1/G'method; Kudryashov transformation; Klein-Gordon equation